2019
DOI: 10.1007/s10712-019-09565-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Ground Penetrating Radar Methods to Investigate Reinforced Concrete Structures

Abstract: This paper provides an overview of the existing literature on the subject of Ground-Penetrating Radar (GPR) methods for the investigation of reinforced concrete structures. An overview of the use of concrete and reinforced concrete in civil engineering infrastructures is given. A review of the main destructive and non-destructive testing (NDT) methods in the field is presented, and an increase in the use of GPR to reinforced concrete structures is highlighted. It was also observed that research in some applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Electromagnetic, elastic wave, optical sensing and infrared thermography methods are widely used in civil engineering for inspecting hard surfaces such as concrete [15,[461][462][463][464]. They are mainly used for determining concrete cover depth and locating rebars with an estimate of their diameter [465].…”
Section: Limitation On the Evaluation Of Corrosion Rate And Interest Of Combining Ndt Methodsmentioning
confidence: 99%
“…Electromagnetic, elastic wave, optical sensing and infrared thermography methods are widely used in civil engineering for inspecting hard surfaces such as concrete [15,[461][462][463][464]. They are mainly used for determining concrete cover depth and locating rebars with an estimate of their diameter [465].…”
Section: Limitation On the Evaluation Of Corrosion Rate And Interest Of Combining Ndt Methodsmentioning
confidence: 99%
“…Those qualitative results confirm this method as a useful tool in corrosion detection, as it presents several advantages over other methods: non-invasive testing, fast data acquisition, and the possibility of survey large areas. The application of GPR to corrosion detection is usually tested in laboratory [21]. However, recent field studies have demonstrated the possibility of obtaining a quantitative approach of damage degree by combining GPR with other NDT survey such as infrared thermography [22].…”
mentioning
confidence: 99%
“…The radar method can also be used to locate reinforcement in concrete. It uses the phenomenon of the penetration and reflection of an electromagnetic wave (in the range of 100 MHz–2 GHz) through a medium (reinforced concrete element) which, depending on the medium material type (concrete or steel), the wave penetrates into depth or is scattered or reflected [ 46 , 47 , 48 , 49 , 50 ]. In the case of the currently used equipment, the method of conducting the research itself is similar to the electromagnetic method, but the interpretation of the results requires more knowledge.…”
Section: Methodsmentioning
confidence: 99%